Access to physiotherapy services in South African settings: stretching a hand to under-resourced communities with students as agents of change - Kganetso Sekome; Laeeqa Sujee; Lauren Tomes; Sonti Pilusa (Frontiers Media S.A., 2023)
BackgroundPhysiotherapy is a healthcare profession that enhances human functioning and prevents further disability. In addition to this physiotherapy promotes health, wellbeing and the prevention of diseases. In South Africa, physiotherapy and rehabilitation services are largely accessed by those living in urban communities and those with private medical funding. Rehabilitation is an essential component of the package of care yet these services do not reach disadvantaged communities who vitally need them. Through the equitable provision of service-learning, physiotherapy students can play a vital role in improving rehabilitation access to vulnerable communities.AimThis paper illustrates how physiotherapy students studying at a South African university provide equitable services to disadvantaged rural and urban communities.DiscussionThe first and second years of study focus on theoretical and classroom-based learning where students gain an understanding of basic principles of inclusion, equity, diversity, and self-awareness. In later years, students provide community-based services in urban and rural communities with a focus on increasing access to rehabilitation services. The clinical objectives which students are required to fulfil are guided by principles of public health and community rehabilitation. The Covid-19 pandemic highlighted the issue of poor access to rehabilitation services and the case study we provide demonstrates the roles physiotherapy students played to fill this gap. The authors offer a reflection from their involvement in physiotherapy student training and provide an example of a moment which displayed equity, diversity, and inclusion in their career.ConclusionThere is a huge gap to fill in the provision of equitable rehabilitation services for the South African population. Institutions responsible for the training of physiotherapists, or any rehabilitation profession, should realize their role in service delivery through a service-learning approach.